Effects of motor games applied in lower primary physical education on the changes of co-ordination abilities of lower primary school children - Reigl, M. (2001)
On the basis of the measuring results I wanted to prove that the pupils receiving regular lessons and are consciously prepared are more successful in the field of co-ordination abilities. The effects of the games prepared by us develop the children in the following areas/fields: movement execution under time pressure condition spatial orientation ability ball handling - ball skills movement awareness/sense of movement total scores of the overall effect on the co-ordination abilities The teachers prepared in many ways could successfully use the game exercises even in difficult conditions. Our work is felt to be successful effective, but we would like to carry out/continue the research, and would like to obtain new result to draw new conclusions from it.